Case report: Cellular therapy for hydroa vacciniforme-like lymphoproliferative disorder in pediatric common variable immunodeficiency with chronic active Epstein-Barr virus infection - Grześk, Elżbieta; Kołtan, Sylwia; Dąbrowska, Anna; Urbańczyk, Anna; Małdyk, Jadwiga; Małkowski, Bogdan; Bogiel, Tomasz; Dębski, Robert; Czyżewski, Krzysztof; Wysocki, Mariusz; Styczyński, Jan (Frontiers in Immunology, 2022)
Hydroa vacciniforme-like lymphoproliferative disorder (HV-LPD) is a cutaneous form of chronic active Epstein-Barrvirus (EBV) infection, which can develop into the extremely rare systemic lymphoma. Patients with Inborn errors of immunity (IEI), such as common variable immunodeficiency (CVID), are at higher risk of developing a severe course of infections especially viral and malignancies than the general population. The aim of the study was to present complex diagnostic and therapeutic management of HV-LPD. The clinical diagnosis was confirmed at the histological and molecular level with next generation sequencing. HV-LPD was diagnosed in a patient with CVID and chronic active Epstein–Barr virus (CAEBV) infection. The patient was refractory to CHOP chemotherapy and immunosuppressive treatment in combination with antiviral drugs (prednisone, bortezomib, gancyclovir). The third-party donor EBV-specific cytotoxic T cells (EBV-CTL, tabelecleucel) were used, which stabilised the disease course. Finally, matched unrelated donor hematopoietic cell transplantation (MUD-HCT) was performed followed by another cycle of EBV-CTL.